Virus Identification in Yard Long Bean Plants with Yellow Mosaic Symptoms - Sutrawati, Mimi; Aulia, Ewa (AGRITROPICA : Journal of Agricultural Sciences, 2024)
Begomovirus infection, which causes yellow leaf curl disease, is commonly found in the Bengkulu province, affecting various plants, including chilli, melon, cucumber, papaya, and weeds. The viruses reported to date in long bean plants include Mungbean yellow mosaic India virus (MYMIV) and Bean common mosaic virus (BCMV). This study aimed to detect viruses in long bean samples collected from Musi Rawas (South Sumatra) and North Bengkulu (Bengkulu), areas where yellow mosaic symptoms resembling those caused by Begomovirus infection were observed. Virus detection was performed using PCR-based DNA analysis with specific MYMIV (MY1/MY2) primers, targeting a DNA fragment of approximately 238 bp. The results revealed that yard-long bean plants from Musi Rawas were positively infected with MYMIV, while those from North Bengkulu tested negative for MYMIV. Begomovirus or other viral infections may cause the yellow mosaic symptoms observed in North Bengkulu yard long beans. Therefore, further investigations using additional primers are needed to identify the specific virus responsible for the symptoms in this region.